Comparison of two high dose rate brachytherapy regimes - Gaurav Jaswal; Raja Benipal; Seema G Bhatty; Pardeep Garg; Manraj S Kang (Wolters Kluwer Medknow Publications, 2023)
Background: Two HDR brachytherapy regimes were compared, 9.5 Gray per fraction for two fractions and 7.5 Gray per fraction for three fractions. Materials and Methods: A total of 80 patients with histologically evident squamous cell carcinoma cervix were taken in the current research after randomization. Radiotherapy dose delivered was 50 Gray/25#/5 weeks with concomitant chemotherapy with weekly cisplatin 35 mg/m2. Following external chemoradiation, patients were randomized into two arms. In Arm A, 40 patients were given high dose rate (HDR) brachytherapy of weekly 7.5 Gray in three fractions over 3 weeks. In Arm B, 40 patients were given high dose rate (HDR) brachytherapy of weekly 9.5 Gray in two fractions over 2 weeks. BED and LQED had been calculated, and the evaluation of response and consequences was examined. Results: In Arm A, BED to point A was 99.38 ± 0.00 and EQD2 to point A was 82.81 ± 0.00. In Arm B, BED to point A was 97.05 ± 0.00 and EQD2 to point A was 80.89 ± 0.00. With respect to rectum in Arm A, BED rectum was 108.66 ± 11.43 and EQD2 rectum was 65.07 ± 6.84. In Arm B, BED rectum was 107 ± 10.83 and EQD2 rectum was 64.21 ± 6.49. Similarly in Arm A, BED bladder was 107.86 ± 10.23 and EQD2 bladder was 64.59 ± 6.13. In arm B, BED bladder was 104.14 ± 10.79 and EQD2 bladder was 62.36 ± 6.46. Conclusion: In a follow-up of 6 months, no statistical significance in terms of local control as well as complications rates in both the arms. Our research demonstrates that two fractions of HDR are comparable with three fractions of HDR.